Assessment of rock musician's efferent system functioning using contralateral suppression of otoacoustic emissions. Issue 4 (1st December 2016) - Kumar, Prawin; Grover, Vibhu; Publius A, Sam; Sanju, Himanshu Kumar; Sinha, Sachchidanand
Abstract : Objective: Contralateral suppression of oto acoustic emission (OAE) is referred as activation of efferent system. Previous literature mentioned about the importance of contralateral suppression of OAEs as a tool to assess efferent system in different groups of population. There is dearth of literature to explore the efferent system function in experienced musicians exposed to rock music using TEOAEs and DPOAEs. Methods: Two groups of participant (14 rock musicians and 14 non‐musicians) in the age range of 18–25 years were involved in the study. Contralateral suppression of TEOAEs and DPOAEs were measured using ILO (Version 6) in both groups. Results: Descriptive statistics showed higher suppression of TEOAEs and DPOAEs in rock‐musicians at most of the frequencies in comparison to non‐musicians. For DPOAE measures, Mann Whitney U test results revealed significantly greater DPOAE suppression only at 1 kHz and 3 kHz in rock‐musicians compared to non‐musicians. For within group comparison, Kruskal Wallis test results revealed there were significant difference observed across most of the frequencies i.e. at 1 kHz, 3 kHz and 6 kHz. For TEOAE measures, Mann Whitney U test results revealed that only at 2 kHz, TEOAE suppression in rock‐musician was significantly greater compared to non‐musicians. Similarly, Kuskal Wallis test results revealed that within group there were no significant differences observed for most of the frequencies except 2 kHz. Conclusions: Based on the above finding, present study concludes that rock musicians are having better efferent system compared to non‐musicians. No suppression effect at few frequencies probably indicates more vulnerability at those frequencies. Contralateral suppression of DPOAE shows more significant finding in comparison to contralateral suppression of TEOAEs in present study.